Estudo comparativo da resistência de união entre resina composta e cerâmica submetida a diferentes tratamentos de superfície - Colares, Regina Cláudia Ramos (2010)
The intraoral repair of ceramic restorations consisted of a clinically effective method for solving fracture of porcelain, and its success depends on quality and durability of the bond between the ceramic and the resin. The purpose of this study was to evaluate the bond strength between lithium disilicate-based ceramic and composite resin when subjected to airborne-particule abrasion with 50 μm aluminum oxide or hydrofluoric acid treatment using two silanization protocols: drying at room temperature or by heating. Twenty blocks (7×7×5mm) of lithium disilicate-based hot-pressed ceramic were fabricated and randomly divided into four groups (n = 5): G1- etched with 9.5% hydrofluoric acid for 20 seconds silanated surface were dried with room-temperature air; G2- treatment performed the same way as G1 employing the drying of the silane surface was 45± 5˚C warm air; G3- airborne-particle abrasion with 50-μm aluminum oxide for 5 seconds and silanated surface was dried 45± 5˚C warm air; G4-treatment performed in the same way that G3 employing drying of silane at room temperature. After an adhesive (Single Bond 2) was applied and before adding 5 mm layers of a composite resin (Filtek Z250), obtaining a block of 10 mm in height. Each blocks ceramic / resin were stored in 37˚C distilled-water for 24 h and cut into ceramic-composite beams with 1mm2 of cross-sectional area for immediately tested by microtensile bond strenght test at a speed of 1 mm / min. Data were analyzed by ANOVA and Student-Newman Keuls (p <0.05). The mean (standard deviation) in MPa were: G1 - 32.14 (7.98), G2 - 35 (7.77) and G3 - 18.36 (6.17). Group 4 can not be assessed because there was a detachment of the resin during the procedure for obtaining specimens. G1 and G2 presented greater tensile strenght than G3 (p<0.05). There was no statistically significant difference between the mean values for groups G1 and G2 (p> 0.05). It was concluded that silane drying by a stream of warm air had an important role in the surface treatment of ceramic with air abrasion.